Evaluasi Sistem Penyimpanan Obat Berdasarkan Standar Pelayanan Kefarmasian Pada Salah Satu Apotek Di Kota Bandung - Sagita DwiDara; Asti Yunia Rindarwati; Raisa N Fadillah; Yoppi Iskandar (Journal of Pharmaceutical and Sciences, 2023)
Storage is an act of storing and securing medicines in a protected place. Drug quality is essential to be maintained through storage. An improper storage system can cause drug ineffectiveness. The research objective was to evaluate the drug storage system at the Bandung Pharmacy. The research method used is descriptive observation, and the evaluation is carried out by observing the activities in the pharmacy. The results showed that the drug storage system in one of the pharmacies in the city of Bandung complies with the Regulation of the Minister of Health of the Republic of Indonesia No. 73 of 2016 concerning Pharmaceutical Service Standards at Pharmacies, which is 80%, where this value is included in the "Good" storage criteria.